Implementation of Demonstration Method in Improving Learning of Azan and Iqamah Material at Muhammadiyah 03 Pekanbaru Elementary School - Gusriani, Wira; Winarti; Sugiarti, Wiwi; Wiwie; Winda (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the effectiveness of the demonstration method in improving student learning outcomes on Azan and Iqamah material in class 2 MI Muhammadiyah 03 Pekanbaru. The demonstration method was chosen because it provides a more concrete learning experience through direct practice, making it easier for students to understand the concepts taught. This study uses a quantitative approach with a classroom action research (CAR) design which is implemented in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Data were collected through observation, learning outcome tests, and interviews with students and teachers to obtain a more comprehensive picture of the effectiveness of this method. The results showed that the application of the demonstration method had a positive impact on student understanding, which was indicated by an increase in the average value from the first cycle to the second cycle. In addition, this method also increased student learning motivation, which was seen from their active participation in the learning process. Students became more enthusiastic and more confident in practicing Azan and Iqamah. Thus, the demonstration method has proven effective in improving the quality of learning Azan and Iqamah material, and can be used as an alternative for teachers in teaching similar material.